PENGEMBANGAN MEDIA PEMBELAJARAN “MATE-MATRIKS” BERBASIS ANDROID MENGGUNAKAN SOFTWARE ADOBE ANIMATE CC - Muhammad Amin Ma’ruf; Nanang Nabhar Fakhri Auliya (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Interactive learning media is a solution that can increase students' interest and motivation in learning mathematics, especially in the discussion of matrices that are often considered difficult by students. The "Mate-Matrix" game was designed with the aim of providing an interesting and interactive learning experience, as well as helping students understand the concept of matrices through a more fun approach. The development method used in the research is the Borg and Gall method. In the development stage, the game was made using Adobe Animate CC software by utilizing the interactive features provided. The implementation process was carried out by testing the game to a number of SMA N 1 Pecangaan students to get feedback that would be used in the evaluation stage. The feasibility test of the Mate-Matrix application was carried out by material experts and media experts. The material expert gave an average score of 91, indicating that the material presented was "very feasible". Media experts gave an average score of 88.5, which is also included in the "very feasible" category. The trial was conducted in small groups (5 students) and large groups (57 students), with each group getting an average score of 80.6 and 88.8. These results show that the Mate-Matrix application falls into the "feasible and "very feasible" category. Based on the results of the feasibility test and trial, it can be concluded that the Mate-matrix learning application can be used as a learning media that is suitable for use in the learning process.